Activation of cardiac sarcoidosis associated with development of gastric cancer: a case report. Issue 2 (12th January 2021) - Kawai, Hideki; Sarai, Masayoshi; Toyama, Hiroshi; Izawa, Hideo
Abstract: Background: The high 18 F-fluorodeoxyglucose (FDG) uptake in sarcoidosis lesions reflects infiltration of inflammatory cells such as macrophages. An increased incidence of cancer in patients with sarcoidosis has been suggested, and some combination of the following mechanisms has been proposed: chronic inflammation, immune dysfunction, shared aetiologic agents, and genetic susceptibility to both cancer and autoimmune diseases. Case summary: A 73-year-old man was admitted to our hospital due to effort dyspnoea. Initial investigations showed complete atrioventricular block on electrocardiography, basal thinning of the interventricular septum, and preserved left ventricular (LV) systolic function on echocardiography, and late gadolinium enhancement (LGE) in all layers of the basal interventricular septum on cardiac magnetic resonance imaging. FDG positron emission tomography/computerized tomography (FDG-PET/CT) showed no abnormal uptake in the whole-body including myocardium. After discussion, corticosteroid was not initiated then. One year later, he developed stomach adenocarcinoma. Repeated investigations demonstrated enlargement of the LV (LV diastolic diameter 63 mm) and diffuse systolic impairment of LV function (LV ejection fraction 31%) on echocardiography, and abnormal focal uptake at the lateral walls of LV and hilar lymph nodes on FDG-PET/CT imaging. One more year after the surgery for gastric cancer and corticosteroid initiation, echocardiography showed recovery of systolic function and FDG-PET/CT showed no uptake in either the myocardium or hilar lymph nodes. Discussion: In the present case, it is speculated that the first inflammation which left scarred areas showing LGE was already completed before the first FDG-PET/CT. The development of gastric cancer may be associated with the reactivation of cardiac sarcoidosis.